Medical biochemistry - Baynes, John W.; Dominiczak, Marek H. (Elsevier Mosby, 1999)
"Medical Biochemistry combines basic science and practical medicine in a concise format that is ideal for future doctors. The content has been carefully crafted to give rigorous coverage of the subject without overloading students, and relevant clinical cases have been threaded throughout." "This new edition of the popular textbook has a new dynamic design incorporating pedagogical special features and four-color illustrations. More clinical material has been integrated into the text, and new clinical test boxes provide a quick reference to the most common laboratory tests."--R?esum?e de l'?editeur.